Application of the Cytochrome-b gene region in Population Study of Striped Snakehead (Channa striata) by Molecular Approach - Andriyono, Sapto; Chaniful Fuadi, Muhammad; Lastuti, Nunuk Dyah Retno (UNIVERSITAS MUHAMMADIYAH PONTIANAK, 2022)
Snakehead fish with different geographical differences can have an impact on genetic diversity. DNA barcoding is a system designed to identify a species precisely and accurately by using short and standardized gene regions. This study aims to determine the diversity of snakehead fish populations in four areas in East Java. This study used the Cytochrome b (Cyt b) gene sequence in mitochondrial DNA to determine genetic variation in the wild population of Channa striata. The results of DNA barcodes with Cytochrome c oxidase subunit I (COI) showed that all samples were validly C. striata species (99.84-99.85%), while Cyt-b sequences had percentage identity with the same sequence species ranging from 99.74 to 100%. The phylogenetic tree reconstructed using MEGAX resulted in a separate clade in the sequences from East Java. This strengthens the similarity of the population of C. striata species in the Brantas watershed.